Development paths for cross-border cooperation and the status quo - Beate Caesar; Karina Pallagst (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
This paper is concerned with the development of cross-border cooperation and its current status. It examines the funding instruments and describes the challenges and opportunities of cross-border cooperation. The paper concludes by discussing some distinctive aspects of cross-border cooperation in spatial planning.
urn:nbn:de:0156-40970279; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Border; cross-border cooperation; spatial planning; challenges; opportunities